The Interactional–Institutional Construction of Teachers’ Emotions in Hong Kong: The Inhabited Institutionalism Perspective - Tsang, Kwok Kuen (Frontiers in Psychology, 2019)
This article illustrates the social construction of teachers’ emotions by drawing on the emergent sociological perspective of inhabited institutionalism to report on a qualitative research project on teachers’ emotions in Hong Kong. A thematic analysis was performed on the transcripts of interviews conducted in 2012 with 21 teachers at Hong Kong secondary schools and on the policy documents and newspaper articles from the education reform era of 1980 to 2011. Three major themes emerged from the data: (1) the institutional logic of whole-personal education, (2) the institutional logic of accountability, and (3) an asymmetry between these institutional logics which is causing a displacement of the meaning of education and thus has emotional consequences for teachers. Taken together, these themes show that managerialist education reforms bring the institutional logic of accountability into the institutional environment of education, which results in the recoupling of school administration and teachers’ work. This recoupling leads to the decline of teachers’ work autonomy. The institutional logic of accountability tends to inhibit the institutional logic of whole-personal education and to replace the instructional meaning of education with managerial meanings. In the institutional context, teachers are forced to do a lot of work that they interpret as meaningless, but they find they are powerless to change the situation. They may therefore choose to inhabit the institutional logic of accountability and the tightly coupled institutional context of school organizations. Consequently, teachers may become unhappy at work during and after managerialist education reforms. According to these findings, teachers’ emotions can be regarded as an interactional-institutional construction. That is, teachers’ emotions may be socially constructed through the negotiation of meaning under the institutional logics that guide their actions and the interactions that uphold the institutional context of the school organizations that they inhabit.